Substantiation of the effectiveness of using a flat mirror concentrator in the solar dryer - Knaga, Jaroslaw; Tatomyr, Andriy; Babych, Mykhailo; Korobka, Serhiy (Eastern-European Journal of Enterprise Technologies, 2017)
We propose a procedure for calculating geometrical parameters of a flat mirror concentrator of solar energy. The procedure describes construction of the path of rays between the mirror and the collector in the form of a system of degree coordinates α. We obtained analytical dependences for the course of illumination of air collector by the sum of direct and reflected flows Еβ(τ) and a flow gain coefficient k. This makes it possible to estimate efficiency of a flat mirror concentrator for different azimuthal angles of orientation of parameters of the horizontal receiving surface of air collector S and the system of degree coordinates α. The rational values for a dihedral angle (focline) α between the mirror and the collector are established, which are 90...120º. It was found that a gain coefficient of the flow of solar energy k is implemented with the least expenditures from 1.8 to 1.2. We report results of experimental research into energy characteristics of work of the mirror concentrator in a combination with an air collector. It was established the application of a mirror concentrator in the solar dryer makes it possible, in the morning and in the evening, to improve annual average capacity of incoming solar radiation on the receiving surface of air collector by an order of 3.41 kW/m2 during daylight. This enables receiving, amplifying, and directing to the absorber of AC from 1.5 to 2.3 kW·h of energy per day from 1 m2 of FMC. The results obtained could be used for design and improvement of technical means of drying, in order to enhance technological and energy efficiency of the process.